Fascin Expression in Ameloblastoma, Odontogenic Keratocyst and Dentigerous Cyst - Sedigheh RAHROTABAN; Nariman NIKPARTO; Parham YOUSEFIZADEH; Mohammad Javad KHARAZIFARD; Samira DERAKHSHAN (Federation of Turkish Pathology Societies, 2018)
Objective: The purpose of this study was to assess and compare fascin expression in 4 lesions which differ in aggressiveness: odontogenic keratocyst, dentigerous cyst and two types of ameloblastoma (solid and unicystic), and to find out whether fascin expression is associated with aggressiveness of these lesions or not. Material and Method: Nine solid ameloblastomas , 12 unicystic ameloblastomas, 13 odontogenic keratocyst and 12 dentigerous cyst were assessed in this study. The slides were examined at x400 magnification. Finally the lesions were divided into two groups based on microscopic examination, "low expression" and "high expression". Results: There were no significant differences between the lesions, except that fascin expression was slightly higher in unicystic ameloblastomas in comparison to other groups in intensity and count of the immunostaining cells. Conclusion: The results of this study suggest that local aggressiveness does not result in fascin expression. We suggest more studies with more samples, assessing expression of different proteins be done in the future.